THE STUDY OF THE IRGANAYSKAYA SETTLEMENT I IN THE CONSTRUCTION ZONE OF IRGANAYSKAYA HYDROELECTRIC POWER STATION IN 2004 IN MOUNTAINOUS DAGESTAN - Ataev, G D (History, Archeology and Ethnography of the Caucasus, 2016)
The article is dedicated to the result archeological researches of lrganai settlement I of the Middle Bronze and the beginning of the Late Bronze age in the area of construction of lrganai hydroelectric power station in 2004
Keywords: ountain Dagestan; Irganay; middle bronze age; culture; settlemen